Potential and Legal Challenges of the Metaverse for Environmental Awareness and Sustainability in Nigeria: A Comparative Analysis with Singapore - Aidonojie, Paul Atagamen; Majekodunmi, Toyin Afolabi; Obieshi, Eregbuonye; Adeyemi-Balogun, Omolola Janet (Administrative and Environtmental Law Review, 2024)
The Metaverse offered a novel and immersive platform where Nigerian users engaged with virtual environments that mirrored the physical world or even transcended its confines, similar to Singapore's adoption in its economy. This digital realm provided a unique opportunity for individuals and organizations to simulate and visualize the environmental consequences of human activities, thereby deepening awareness of ecological issues. Virtual reality simulations and immersive educational experiences empowered users to witness the ramifications of environmental degradation, motivating them to adopt eco-friendly practices in their daily lives. However, the realization of the Metaverse's potential for promoting environmental awareness and sustainable practices faced various legal challenges. This research employed a hybrid research approach, combining both doctrinal and non-doctrinal methods, to assess the prospects and legal issues surrounding the use of the Metaverse as a catalyst for environmental awareness and sustainability. A total of 304 questionnaires were distributed to Nigerian respondents, and data were analyzed using descriptive and analytical methods. The findings revealed that the burgeoning Metaverse had the potential to play a pivotal role in advancing environmental awareness and sustainable practices, contributing to the mitigation of climate change. Nonetheless, several challenges, such as data privacy, security issues, regulatory concerns related to the Metaverse, digital illiteracy, and insufficient funding for incorporating Metaverse technology, might hinder its effective utilization for promoting environmental awareness and sustainability. It was concluded that the Metaverse possessed transformative power to enhance environmental awareness and sustainable practices in Nigeria. Furthermore, drawing insights from Singapore's experiences in the Metaverse highlighted potential lessons and inspiration for Nigeria as it embarked on this journey of environmental awareness and sustainability through immersive digital experiences.